Nilai Moral dalam Novel Seperti Dendam, Rindu Harus Dibayar Tuntas Karya Eka Kurniawan dan Implikasinya terhadap Pembelajaran Pembelajaran di SMA - Muhammad Amiruddin; Leli Triani; Syamsul Anwar (Journal on Education, 2023)
The purpose of this study is to describe the moral values in the novel Like Dendam, longing to be paid in full by eka Kurniawan's work and the implications for learning in high school. This study uses a qualitative method. Sources of data obtained from novels such as revenge, longing must be paid in full. Data collection techniques used by researchers are listening and note-taking techniques. The data analysis technique used a descriptive analysis study. The technique of presenting the results of data analysis using informal methods. The results of the study show that the moral values in the novel such as revenge longing must be paid in full with a total of 23 data. This research on moral values is implicated in learning Indonesian in SMA class XII even semester on basic competence 3.11 about analyzing messages from a fiction book that is read.